New PB-isotopic constraints on the age of the moon - Snape, J.; Nemchin, Alexander; Bellucci, J.; Whitehouse, M.; Tartese, R.; Barnes, J.; Anand, M.; Crawford, I.; Joy, K. (WILEY-BLACKWELL, 2015)
New noble gas data for several recently found martian meteorites will be presented to determine cosmic-ray exposure ages and source pairing. The presence of trapped (atmospheric) components and discrepancies to earlier data sets will be discussed.